2017
DOI: 10.1002/ppul.23910
|View full text |Cite
|
Sign up to set email alerts
|

Is secretion of IFN‐gamma in response to Mycobacterium tuberculosis antigens in youngest children sufficient to play a role in TB diagnostics?

Abstract: The youngest children release sufficient amount of IFN-ɣ in response to TB antigens thus QFT-GIT might be a useful tool for TB diagnostics in this age group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
2
6
0
1
Order By: Relevance
“…Following a positive result of any of the above-mentioned tests, a chest X-ray must follow. Abnormalities indicating tuberculosis compel further diagnostic investigations that involve bacteriological tests ( Bielecka et al 2018a ; 2018b ). According to The Polish Respiratory Society, children with TB contact should be treated even if TST and IGRA results are negative ( Augustynowicz-Kopeć et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Following a positive result of any of the above-mentioned tests, a chest X-ray must follow. Abnormalities indicating tuberculosis compel further diagnostic investigations that involve bacteriological tests ( Bielecka et al 2018a ; 2018b ). According to The Polish Respiratory Society, children with TB contact should be treated even if TST and IGRA results are negative ( Augustynowicz-Kopeć et al 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“… Seddon et al (2016) observed that BCG vaccination affected TST response in children aged < 5 years with a negative IGRA result, but the effect disappeared with age. In Poland, to improve the sensitivity of LTBI diagnostics in children, two tests are used: TST and IGRA (QFT or T-SPOT.TB) ( Augustynowicz-Kopeć et al 2013 ; Bielecka et al 2018a ; 2018b ). Importantly, Buonsenso et al (2020) reported that QFT-Plus could be particularly useful for the evaluation of children with suspected LTBI, giving only a 2.5% rate of indeterminate results in pediatric group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…У пацієнтів із ЛТІ кореляція виявилася ще більш сильною. Тому автори дійшли висновку, що найменші діти виділяють достатню кількість гамма-інтерферону у відповідь на туберкульозні антигени, тому КФТ може бути корисним інструментом для діагностики ЛТІ в цій віковій групі [19].…”
Section: квантифероновий тест у дітейunclassified
“…Infection. However, they perform less reliable in human immune virus (HIV)-infected and young children, albeit with inconsistent results [6][7][8][9] . Neither test discriminates ATB from LTBI, nor are they licensed for ATB diagnosis.…”
mentioning
confidence: 99%